Cage Sanitation, Hygiene of Dairy Farmer, Physical Quality and Microorganism of Dairy Cattle Milk In Medowo, Kediri, East Java - Bahrul Fawaid (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: The cage sanitation and hygiene of dairy farmer were important to be maintained in order to keep the physical quality and microorganisms of the milk. This research was conducted to analyze the cage sanitation, hygiene of dairy farmer, physical quality and microorganisms in the milk from dairy farmers in Medowo, Kediri, East Java. Method: This research was a observational research with cross sectional design. The sample of population total was 26 of dairy farmer that registered of Kertajaya Village Unit Cooperative in Ringinagung Village, Medowo Village, Kandangan District, Kediri Region. The variables of this research were cage sanitation, the farmer's hygiene and physical quality and the microorganisms in the milk including Total Plate Count (TPC) and E. coli. The data were obtained through interviews and direct observation using a questionnaire and examination of milk microorganisms in the veterinary public health laboratory of the Livestock Service Office of East Java Province. Data were analyzed descriptively. Result and Discussion: This research found that the sanitary of the cage were classified as excellent (92%), the farmer's hygiene was considered as inadequate with (69%), the physical quality of the milk which include smell, taste and color were 100% in good condition, except in one sample (3,8%) of the milk contained a TPC that exceeded in standar (1 x 106 cfu / ml). The number of milk samples contaminated by E. coli were 7 samples (27%). Conclusion: Improving hygiene and sanitation can avoid cross contamination between pathogenic microorganisms in the milk quality.